The Effects of hospital based respiratory physiotherapy an intervention study among COPD patient in Al-Zawia City, Libya - Zafar Ahmed,; Sharifa Ezat Wan Puteh,; Aisha Abdussalam,; Mahmud Hanesh,; Suriati Sukeri,; Leonard Joseph, (Universiti Kebangsaan Malaysia, 2012)
Chronic obstructive pulmonary disease (COPD) is a one of the major cause of death and disability worldwide. This study aimed to compare the quality of life (QOL), Activity of Daily Living (ADL), Pulmonary Function Test (PFT) and general health symptoms pre and after hospital-based respiratory physiotherapy program among COPD patients. Methods Pre and post intervention study was conducted between January and July 2010. A total of 54 subjects aged between 30 to 40 years old were recruited for this study using universal sampling method from Alzawia Teaching Hospital, Libya. Data collected were socio-demographic data, QOL (before and after the intervention) using the Short Form-36 (SF-36) questionnaire, ADL using the Barthel Index and the General Health Symptoms. Results The mean SF-36 score for QOL is 30.13 (SD = 8.06) and 63.46 (SD = 13.53) before and after the physiotherapy respectively (with the p <0.0001). Patients’ Activity of Daily Living mean scores are 70.18, (SD = 16.50) and mean = 88.89 (SD = 13.28) before and after program (p< 0.0001). The general medical condition mean score after respiratory physiotherapy is 3.72 as compared to 4.96 before the respiratory physiotherapy (p< 0.0001). Pulmonary Function Test shows improvement in actual/predicted FEV1 ratio in all 54 cases with mean improvement from 55.85 before to 81.67 after the pulmonary physiotherapy (with the p <0.0001). Conclusions Hospital based respiratory physiotherapy program had significantly improved QOL, pulmonary function and activities of daily living among the subjects.